Investigation of Dry Eye Symptoms in Health Workers of National Medical College and Teaching Hospital following Corona Virus Pandemic - Bista, Padam Raj; Bista, Bipin; Mishra, Surendra; Yadav, Reena; Chaudhary, Sushma; Gupta, Sharad (Med Phoenix, 2021)
Background: With the outspread of global pandemic Corona virus disease 19. (COVID-19), use of face masks was taken as a vital deed against severe acute respiratory syndrome coronavirus-2. (SARS-CoV-2) The aim of this study was to assess symptoms of mask associated dry eye (MADE) among health workers. Materials and Methods: A total of 169 heath workers meeting the inclusion criteria were selected by simple random sampling from respective department. Data were obtained by providing with questionnaire established by the researcher and Ocular Surface Disease Index (OSDI) to the participants from November 1, 2020 to March 31, 2021 at National Medical College and Teaching Hospital. The data were evaluated using correlation test. Results: A total of 169 heath workers were enrolled in the study. The mean age of the patient was 31.74±7.34 years (range 19-56).According to OSDI, 27(15.9%) of the participants had mild dry eye symptoms followed by 15 (8.87%) cases of moderate and 44(26.03%) of severe respectively. Duration of mask wearer and electronic devices usage were two variables that were statistically correlated with OSDI (p<0.01). The OSDI was not statistically correlated with age, glass wear and sleep duration. Conclusion: With the emergence of COVID -19, measures to cope against this pandemic are must. With the increasing use of controlling measures, it is prime responsibility of ophthalmic faculty to start awareness regarding proper use of these anti-COVID measures and make sustainable environment in future.